piRNA pathway gene expression in the malaria vector mosquito Anopheles stephensi - Macias, V (BlackWell Publishing Ltd, 2014)
The ability of transposons to mobilize to new places in a genome enables them to introgress rapidly into populations. The piRNA pathway has been characterized recently in the germ line of the fruit fly, Drosophila melanogaster, and is responsible for downregulating transposon mobility. Transposons have been used as tools in mosquitoes to genetically transform a number of species including Anopheles stephensi, a vector of human malaria. These mobile genetic elements also have been proposed as tools to drive antipathogen effector genes into wild mosquito populations to replace pathogen-susceptible insects with those engineered genetically to be resistant to or unable to transmit a pathogen. The piRNA pathway may affect the performance of such proposed genetic engineering strategies. In the present study, we identify and describe the An. stephensi orthologues of the major genes in the piRNA pathway, Ago3, Aubergine (Aub) and Piwi. Consistent with a role in protection from transposon movement, these three genes are expressed constitutively in the germ-line cells of ovaries and induced further after a blood meal.